Cu2O as a Potential Intermediate Transparent Conducting Oxide Layer for Monolithic Perovskite‐CIGSe Tandem Solar Cells. Issue 10 (12th October 2017) - Wang, Yajie; Steigert, Alexander; Yin, Guanchao; Parvan, Vladimir; Klenk, Reiner; Schlatmann, Rutger; Lauermann, Iver
Abstract : Constructing tandem junction devices consisting of a bottom cell based on prevailing solar cell techniques such as silicon (Si) or Cu(In, Ga)(Se, S)2 (CIGS) combined with a perovskite top cell is one effective approach to improve photovoltaic device performance. An intermediate transparent conducting layer as one component of the tunnel junction connecting the two single devices, at the same time serving as inorganic hole transport material for the perovskite solar cell is one of the key components to realize a perovskite‐CIGSe tandem structure. In this contribution, we describe the deposition of p‐type Cu2 O films at room temperature by magnetron sputtering using nitrogen doping to form a homogenous layer with high transparency and good conductivity, and the modeling of a monolithic perovskite‐CIGSe tandem solar cell utilizing this layer. We applied the in‐house software RefDex to illustrate the impact of Cu2 O on the performance of a tandem device, and calculated the reflection, transmission, and absorption. Abstract : P‐type transparent conducting oxide Cu2 O as one component of the tunnel junction connecting the two single devices for monolithic perovskite‐CIGSe tandem solar cells shows good properties and good energy level alignment with perovskite‐CIGSe tandem structures.